Hypomethylating agent combination strategies in myelodysplastic syndromes: hopes and shortcomings. Issue 5 (4th May 2017) - Ball, Brian; Zeidan, Amer; Gore, Steven D.; Prebet, Thomas
Abstract: The hypomethylating agents (HMA) azacitidine and decitabine are both approved by the FDA for the treatment of myelodysplastic syndromes (MDS). Although heralded as a significant advancement, HMA lead to responses in less than half of patients and for those that respond most will relapse. As such, there is a crucial need to improve frontline therapy approaches. One promising strategy involves combining azacitidine or decitabine with investigational or existing therapies with the goal of achieving synergistic activity and better patient outcomes. The purpose of this paper is to critically review the efficacy and safety of reported HMA-based combination regimens in patients with higher-risk MDS.